2019
DOI: 10.1021/acsami.8b20884
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Dependent Hole Transfer under Negligible HOMO Difference in Non-Fullerene Acceptor-Based Ternary Polymer Solar Cells

Abstract: In the field of organic solar cells, it has been generally accepted until recently that a difference in band energies of at least 0.3 eV between the highest occupied molecular orbital (HOMO) level of the donor and the HOMO of the acceptor is required to provide adequate driving force for efficient photoinduced hole transfer due to the large binding energy of excitons in organic materials. In this work, we investigate polymeric donor:non-fullerene acceptor junctions in binary and ternary blend polymer solar cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The photoinduced charge transfer at the interface and the subsequent carrier transport lies at the heart of the operation and performance of OSCs. ,, These dynamic processes are controlled by donor/acceptor molecular properties (e.g., structures and energetics) and phase morphology properties (e.g., domain size and phase segregation). ,,, Compared to fullerene OSCs, the hole transfer (HT) from photoexcited NFAs is important to device performance but still largely unexplored. Efficient HT has been observed from NFAs to polymer donors with a small energy offset. ,,,,, It has been demonstrated that by tuning molecular energy levels and structures, HT efficiency and thus PCE of OSC devices can be enhanced. ,,,,, Despite these intense researches from molecular aspects, a correlation between HT process and macroscopic NFA phase properties is still lacking.…”
mentioning
confidence: 99%
“…The photoinduced charge transfer at the interface and the subsequent carrier transport lies at the heart of the operation and performance of OSCs. ,, These dynamic processes are controlled by donor/acceptor molecular properties (e.g., structures and energetics) and phase morphology properties (e.g., domain size and phase segregation). ,,, Compared to fullerene OSCs, the hole transfer (HT) from photoexcited NFAs is important to device performance but still largely unexplored. Efficient HT has been observed from NFAs to polymer donors with a small energy offset. ,,,,, It has been demonstrated that by tuning molecular energy levels and structures, HT efficiency and thus PCE of OSC devices can be enhanced. ,,,,, Despite these intense researches from molecular aspects, a correlation between HT process and macroscopic NFA phase properties is still lacking.…”
mentioning
confidence: 99%
“…In contrast, by incorporating a blend of IT-4F and NC 70 BA into PBDB-T-2F (the optimized ternary ratio), the η value is further decreased (the η value is 0.87 ns), which is attributed to the more efficient exciton dissociation within the optimized PBDB-T-2F:IT-4F:NC 70 BA ternary film . The exciton dissociation efficiency ( E ) can be estimated by the following equation where η neat and η blend are the fluorescence lifetimes of the neat and blend films, respectively. The exciton dissociation efficiency is 78.78% for the optimized ternary film and is higher than that of the PBDB-T-2F:IT-4F binary film (the efficiency is 75.37%) .…”
Section: Results and Discussionmentioning
confidence: 86%
“…That result can be ascribed to smooth LUMO level interface and small barrier at the m ‐ITIC/ITIC‐Th interface. Thus, current injected at the two direction for the electron‐only device exhibited clearly demonstrated bilateral symmetry (from the ITO to Al electrode and from Al to ITO electrode) and favor to suppress the electron recombination at the m ‐ITIC:ITIC‐Th interfaces …”
Section: Resultsmentioning
confidence: 97%